Pengelolaan Limbah Pupuk Organik Cair Dari Feses dan Urine Kambing di Kelompok Ternak Telaga Risky, Kota Metro, Lampung - Imelda Panjaitan; Nurhayati Nurhayati; Tri Rumiyani; Neko Riffiandi; Susanti Susanti; I Putu Ajie Windu Kertayoga (Jurnal Pengabdian Masyarakat (abdira), 2022)
The purpose of community service activities for waste treatment technology in the Telaga Rizky goat breeder group is to transfer waste processing technology, namely the manufacture of Liquid Organic Fertilizer so that farmers can overcome their waste control problems. The method of activities carried out in this service is monologue, grant, and practice. The transfer of technology for handling and processing waste at the Telaga Rizky goat breeder group really helps farmers in dealing with waste problems which have been a problem for them so far. In addition, they can also increase their income through the waste products they process.